PENGARUH CITRA MEREK, HARGA, KUALITAS PRODUK DAN VARIASI PRODUK TERHADAP MINAT BELI ULANG ICE CREAM MIXUE PADA MASYARAKAT KOTA MEDAN - Hsb, Dinda Namira; Nurbaiti, Nurbaiti; Imsar, Imsar (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.14.NO.01.TAHUN.2025DO - 10.24843/EEB.2025.v14.i01.p06, 2025)
This study aims to analyze the effect of brand image, price, product quality, and product variety on repurchase interest in Mixue ice cream in Medan City, both partially and simultaneously. The research sample consisted of 97 respondents, with quantitative methods and purposive sampling techniques. Data analysis was carried out using multiple linear regression with the SmartPLS application and Structural Equation Modeling (SEM) techniques. The results showed that brand image, price, and product variety had a positive and significant effect on repurchase intention, while product quality had no significant effect. The implication of this research is that consumers should be more selective in choosing products, by considering factors other than price, such as brand image, quality, and product variety.